The Effect of Different Chewing Gum on pH of Dental Plaque - Mirzakhani, Mahboobeh; Amir Siavashani, Manousha; Seyyed Akhavan, Parisa (Journal of Dental School, 2019)
Objective: Although the most useful method to reduce mechanical dental plaque is brushing and flossing, but due to the lack of adequate effectiveness achieved by these methods, the use of other methods such as replacing sweeteners, including Xylitol and Sorbitol with sucrose in products such as chewing gums have come into the focus of attention. This research was done aimed at examine the effect of gum types containing Xylitol, Calcium and Xylitol or Sorbitol on dental plaque pH changes. Methods: The study was performed as a randomized, single-blind, cross-over clinical trial on 10 female students with an age range of 20 to 30 years old studying in dental school, Azad University. Plaque pH changes were measured using PH Meter device after taking four types of chewing gums containing Xylitol, Sorbitol, Xylitol+ Calcium, Turpentine and 10% sucrose solution as control in the follow-up periods. To compare pH at any time between different materials, the Cried-mann test was used. For group pair comparison, Wilcoxon-signed rank test and Bone-Serroni-Adjusment test were used. Results: Xylitol had the highest average plaque pH during the period time that pH increase at minute 7 was the maximum, and turpentine had the lowest pH at all moments, which reached to its maximum at minute 2 and showed little change in plaque pH increase up to minute 60. The difference between all four types of materials was significant (p<0.001). Conclusion: The use of chewing gum after drinking sugar syrup caused a significant plaque pH increase within 7 minutes up to the initial normal level that the effect of Xylitol chewing gum was significantly higher than the rest.